2007
DOI: 10.1126/science.1135009
|View full text |Cite|
|
Sign up to set email alerts
|

Ultrafast Bond Softening in Bismuth: Mapping a Solid's Interatomic Potential with X-rays

Abstract: Intense femtosecond laser excitation can produce transient states of matter that would otherwise be inaccessible to laboratory investigation. At high excitation densities, the interatomic forces that bind solids and determine many of their properties can be substantially altered. Here, we present the detailed mapping of the carrier density–dependent interatomic potential of bismuth approaching a solid-solid phase transition. Our experiments combine stroboscopic techniques that use a high-brightness linear el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
267
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 372 publications
(303 citation statements)
references
References 23 publications
(34 reference statements)
30
267
1
Order By: Relevance
“…This is a displacive excitation and occurs in a sub-picosecond time scale. [2][3][4] A shear structural deformation of the unit cell is necessary to complete the transition, whose time scale is determined by the excitation of acoustic phonons via anharmonic decay of optical phonons; at room temperature it occurs in 12 ps. 5 These changes are expressed in the following rate equations model: k is the rate constant for the ' α β  transition mediated by the shear distortion; and th k is the rate constant for reaching the thermal equilibrium.…”
Section: Rate Equations Modelmentioning
confidence: 99%
“…This is a displacive excitation and occurs in a sub-picosecond time scale. [2][3][4] A shear structural deformation of the unit cell is necessary to complete the transition, whose time scale is determined by the excitation of acoustic phonons via anharmonic decay of optical phonons; at room temperature it occurs in 12 ps. 5 These changes are expressed in the following rate equations model: k is the rate constant for the ' α β  transition mediated by the shear distortion; and th k is the rate constant for reaching the thermal equilibrium.…”
Section: Rate Equations Modelmentioning
confidence: 99%
“…Recently there has been considerable interest in the dynamics of the A 1g mode in the limit of a dense electronhole plasma, particularly for bismuth [21][22][23][24][25][26][27][28][29] . Hase et al 24 observed that the frequency of the mode is impulsively softened and chirped toward the equilibrium value over a few picoseconds.…”
Section: Introductionmentioning
confidence: 99%
“…This motion can be tracked in the time domain by measuring the effects of the coherent phonons on the transient reflectivity of a material and has been used extensively as a probe to study the lattice in near-equilibrium conditions in the vicinity of phase transitions 11 , as well as to look at phonon softening [12][13][14] and hardening 15 when the system is strongly driven. Phonon softening or hardening results from a change in the curvature 16,17 of the lattice potential, but not from a change in the symmetry of the potential. When the symmetry changes, the number of modes typically changes, which may occur when a soft phonon mode tends to zero frequency for a second-order phase transition 14 or may be step-like for a first-order phase transition.…”
mentioning
confidence: 99%